Maine Implements the Clean Air Act: Federalism, Environmentalism and Interest Group Accountability - Reisman, Jon (Maine Policy Review, 1996)
The implementation of environmental policy initiatives often brings about a complex interplay between science and policy, public opinion, interest groups, federal and state mandates, and political machination. Jon Reisman uses Maine’s recent experience of compliance with the 1990 Clean Air Act to illustrate this complexity. In doing so, he addresses several important, but often ignored, issues, such as stakeholder participation in the policy making process, interest group accountability to implementation, and the long term consequences to the environment if these issues are avoided.
Keywords: Maine; Clean Air Act